Representation of Violence and Resistance of Female Characters in the Perempuan Tanah Jahanam - Mukminin, Muhamad Saiful (Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
In literary works, women are often portrayed as subjects who have no power, making them vulnerable to violence. Resistance is also carried out as an effort made by women in dealing with the violence experienced. This study aims to describe the forms of violence and resistance carried out by female characters in the movie Perempuan Tanah Jahanam. This research is descriptive qualitative research with an objective approach that focuses on literary works. The data in this study are in the form of dialog and excerpts of scenes that represent forms of violence and resistance efforts of female characters in the face of violence. The data collection technique used is library technique and analyzed with descriptive analytic technique. The results of this study show that in Perempuan Tanah Jahanam, there are three forms of violence experienced by female characters, including physical, psychological, and sexual violence. The efforts of female characters in dealing with the violence are depicted through open and closed resistance. The open form of resistance is threatening with words and sharp weapons, while the closed resistance is hiding, running away, and seeking help.